2017
DOI: 10.1158/0008-5472.can-16-1656
|View full text |Cite
|
Sign up to set email alerts
|

HER2 and EGFR Overexpression Support Metastatic Progression of Prostate Cancer to Bone

Abstract: Activation of the epidermal growth factor receptors EGFR (ErbB1) and HER2 (ErbB2) drive the progression of multiple cancer types through complex mechanisms that are still not fully understood. In this study, we report that HER2 expression is elevated in bone metastases of prostate cancer independently of gene amplification. An examination of HER2 and NF-κB receptor (RANK) coexpression revealed increased levels of both proteins in aggressive prostate tumors and metastatic deposits. Inhibiting HER2 expression in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 49 publications
2
122
0
Order By: Relevance
“…The poor results of treatment for malignant SGC has given rise to an ongoing search for novel, personalized therapeutic approaches. In many cancers, overexpression of certain proteins has been shown to play a crucial role in cancer pathogenesis and disease progression . For example, in prostate cancer, there is substantial evidence for the overexpression of AR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor results of treatment for malignant SGC has given rise to an ongoing search for novel, personalized therapeutic approaches. In many cancers, overexpression of certain proteins has been shown to play a crucial role in cancer pathogenesis and disease progression . For example, in prostate cancer, there is substantial evidence for the overexpression of AR .…”
Section: Discussionmentioning
confidence: 99%
“…In many cancers, overexpression of certain proteins has been shown to play a crucial role in cancer pathogenesis and disease progression. 9,10 For example, in prostate cancer, there is substantial evidence for the overexpression of AR. 11 Although only limited data are available in SGC, the studies published to date suggest that, similar to prostate cancer, AR is the most commonly expressed receptor in these tumors.…”
Section: Overexpression Of Arsmentioning
confidence: 99%
“…5,6 Therefore, investigations of novel therapeutic target molecules outside of AR signaling pathways are needed to develop new therapeutic strategies for CRPC and progressive prostate cancer. Day et al 7 reported that epithelial cell growth factor (EGF) and its receptor (EGF-R) are expressed in prostate cancer tissue and that expression levels of these proteins correlate with survival rate. Furthermore, other growth factors such as vascular endothelial growth factor (VEGF) and insulin-like growth factor (IGF) are related to prostate cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…M any human cancers are caused by the accumulation of somatic mutations in oncogenes that confer selective growth advantage. The epidermal growth factor receptor (EGFR) kinase is one such oncogene that is mutationally activated in many human cancers, in particular lung cancer (1)(2)(3)(4). Cancer genome sequencing studies have revealed numerous genomic alterations in EGFR, including point mutations, deletions, and insertions (5)(6)(7).…”
mentioning
confidence: 99%